Pedestrian Safety in Frontal Tram Collision, Part 1: Historical Overview and Experimental-Data-Based Biomechanical Study of Head Clashing in Frontal and Side Impacts - Lopot, Frantisek; Tomsovsky, Lubos; Marsik, Frantisek; Masek, Jan; Kubovy, Petr; Jezdik, Roman; Sorfova, Monika; Hajkova, Barbora; Hylmarova, Dita; Havlicek, Martin; Stocek, Ondrej; Doubek, Martin; et al. (Sensors (Basel, Switzerland), 2023)
This article represents the first paper in a two-part series dealing with safety during tram-pedestrian collisions. This research is dedicated to the safety of trams for pedestrians during collisions and is motivated by the increased number of lethal cases. The first part of this paper includes an overview of tram face development from the earliest designs to the current ones in use and, at the same time, provides a synopsis and explanation of the technical context, including a link to current and forthcoming legislation. The historical design development can be characterised by three steps, from an almost vertical front face, to leaned and pointed shapes, to the current inclined low-edged windshield without a protruding coupler. However, since most major manufacturers now export their products worldwide and customisation is only of a technically insignificant nature, our conclusions are generalisable (supported by the example of Berlin). The most advantageous shape of the tram's front, minimising the effects on pedestrians in all collision phases, has evolved rather spontaneously and was unprompted, and it is now being built into the European Commission regulations. The goal of the second part of this paper is to conduct a series of tram-pedestrian collisions with a focus on the frontal and side impacts using a crash test dummy (anthropomorphic test device-ATD). Four tram types approaching the collision at four different impact speeds (5 km/h, 10 km/h, 15 km/h, and 20 km/h) were used. The primary outcome variable was the resultant head acceleration. The risk and severity of possible head injuries were assessed using the head injury criterion (HIC15) and its linkage to the injury level on the Abbreviated Injury Scale (AIS). The results showed increasing head impacts with an increasing speed for all tram types and collision scenarios. Higher values of head acceleration were reached during the frontal impact (17-124 g) compared to the side one (2-84 g). The HIC15 values did not exceed the value of 300 for any experimental setting, and the probability of AIS4+ injuries did not exceed 10%. The outcomes of tram-pedestrian collisions can be influenced by the ATD's position and orientation, the impact speed and front-end design of trams, and the site of initial contact.
Keywords: safety; front face design; Pedestrians; tram; Accidents, Traffic; collision; crash test; motorová vozidla; lidé; head injury criterion; Wounds and Injuries; Craniocerebral Trauma; chodci; Motor Vehicles; Walking; pedestrian; windshield; rány a poranění; chůze; dopravní nehody; kraniocerebrální traumata; Humans